"The role of the educational discipline "History of Ukrainian Statehood and Culture" in the vocational training of officers-specialists in working with personnel" - Vasylchenko , R. (Problems of Engineer-Pedagogical Education, 2023)
The scientific article discusses the role of the educational discipline "History of Ukrainian Statehood and Culture" in the training of future officers as personnel specialists. The article examines the peculiarities of Ukrainian history and culture, substantiates the need to study the stages of the formation of Ukrainian statehood. Peculiarities of the professional activity of officers in working with personnel are considered. Modern scientific assets from the history of Ukraine are analyzed. The decisive role of the discipline "History of Ukrainian Statehood and Culture" in the formation of national identity is determined. The paper considers how knowledge of the history and culture of Ukraine contributes to the formation of awareness, patriotism and cultural development of future officers. A conclusion is made about the influence of this discipline on the understanding of the peculiarities of Ukrainian national identity and its influence on military service. The article examines the importance of learning the historical aspects of Ukrainian culture for the formation of a deep understanding of the national heritage, and the role of this understanding when interacting with personnel. The article discusses the influence of historical knowledge on the professional development of officers and their ability to solve complex tasks in the conditions of military operations and international cooperation. It is concluded that knowledge of the history and culture of one's country is an important factor for improving the moral and ethical components of the personality of officers. Additionally, knowledge of the history and culture of Ukraine can raise the morale of officers, as well as increase responsibility and efficiency when interacting with personnel. The scientific article emphasizes the importance of studying the history and culture of Ukraine in the process of training officers, as a key element of their vocational training and making a positive contribution to the development of the military sphere and national security of the country. It is argued that the knowledge of the history and culture of one's country is an important factor for improving the moral and ethical position of officers, and makes it possible to perform duties at a high professional level.